Hyperbaric oxygen therapy a boon for complex post traumatic wounds - Vagholkar, Ketan; Sharma, Arya; Malik, Mehnish; Garg, Siddharth; Siddhartha, Volam; Purandare, Tanay (International Surgery Journal, 2023)
Post-traumatic wounds especially after run over accidents are difficult to manage. The vascularity and regenerative potential of the tissues is severely compromised. Surgical intervention is of limited value. A conservative approach with concomitant hyperbaric oxygen therapy (HBOT) serves as a great salvage in such cases. A case of post-traumatic forefoot gangrene in a 27-year-old laborer is presented to highlight and create an awareness of the potential benefit of HBOT in salvage of distal parts of the lower extremity where the blood supply is severely compromised.